Interventions to address household food insecurity in high-income countries. Issue 3 (27th March 2018) - Loopstra, Rachel
Abstract : Household food insecurity is a serious public health concern in high-income countries. Canada and the USA regularly monitor household food insecurity, while in other countries, such as the UK, it has been the rapid rise of food bank usage that has drawn increased attention to this longstanding, but largely overlooked, problem. This review evaluates evidence on interventions intended to reduce household food insecurity in high-income countries. Research on social protection interventions suggests both cash transfers and food subsidies (e.g. the US Supplement Nutrition and Assistance Programme) reduce household food insecurity. In contrast, research on community-level interventions, such as food banks and other food programmes, suggests limited impacts. Although food banks have become a common intervention for food insecurity in high-income countries, evidence suggests their reliance on donations of volunteer time and food make them inevitably limited in the assistance they are able to provide. The stigma people feel using food banks may also make them untenable. Alternatives to, or enhanced, food banks such as community shops or community kitchens, have become common, but evidence also suggests they may be limited in effectiveness if they do not reach people experiencing food insecurity. This review highlights the difficulty of trying to address household food insecurity with community-based food interventions when solutions likely lie upstream in social protection policies.